WHAT MADURESE CAN TELL US ABOUT OTHER LANGUAGES AND WHAT OTHER LANGUAGES CAN TELL US ABOUT MADURESE - D. Davies, William (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
There are many reasons to study a particular language. One might study a language to learn to speak that language in order to be able to communicate with native speakers or conduct business. One can study a language to learn about the culture of the people or understand their literature and poetry. One can study the grammar of a language to understand the structure of that language and compare it to the structure of other languages It is this last reason that motivates the following discussion.